Mutations affecting the superantigen activity of staphylococcal enterotoxin B. - Briggs, C (1997)
As a superantigen, staphylococcal enterotoxin B (SEB) possesses the ability to bind to major histocompatibility complex class II molecules and be recognized by T cells bearing certain T-cell receptor (TCR) V beta alleles. Other investigators have utilized site-specific mutagenesis to generate amino acid substitutions to identify residues that may be involved in the interaction with the TCR beta-chain. In an attempt further to define the face of the SEB molecule involved in the interaction with the beta-chain, we have employed a polymerase chain reaction (PCR)-based, site-specific mutagenesis method to generate amino acid substitutions with altered superantigen activity. Our results show that valine at position 169 appears to be involved in the function of this superantigen, since each of several substitutions at this position exhibit a significantly reduced ability to induce T-cell proliferation. Analysis of the responding T cells to the residue 169 substitution shows that the mutant toxins maintain TCR V beta selectivity. At the same time, mutation of the proximal histidine at position 166 does not alter the superantigen activity of SEB. Radiolabelled binding analysis of these H166 and V169 mutants shows that class II-binding activity is not significantly altered. When viewed in the context of other results reported in the literature, combined with the crystal structure of the toxin, our results suggest that the interaction with the TCR probably involves SEB residues which ring a cavity along one side of the toxin molecule.